Antimicrobial activity and cytotoxicity of xanthoquinodin analogs from the fungus Cytospora eugeniae BCC42696. (July 2018) - Sadorn, Karoon; Saepua, Siriporn; Boonyuen, Nattawut; Boonruangprapa, Tanapong; Rachtawee, Pranee; Pittayakhajonwut, Pattama
Abstract: Eleven previously undescribed compounds, including cytosporanthraxanthone, xanthoquinodins A7–A10, ketoxanthoquinodin A6, xanthoquinodins B6–B8, and spiroxanthoquinodins A and B, and one synthetically known compound, 2-methoxy pinselin, as well as ten known compounds, including xanthoquinodins A4−A6, B4, and B5, chrysophanol, physcion, (4 S )-5-hydroxy-4-methoxy-α-tetralone, (4 S )-4, 8-dihydroxy-α-tetralone (or isosclerone), and gonytolide C were isolated from the fungus Cytospora eugeniae BCC42696. Their chemical structures were determined based on the analysis of NMR spectroscopic and mass spectrometric data. Moreover, the absolute configurations of the unknown compounds were established by using NOESY and NOEDIFF NMR experiments along with CD spectroscopic data. The isolated xanthoquinodins exhibited a broad range of antimalarial, antibacterial, and fungicidal activities as well as cytotoxicity. Xanthoquinodins A6, B4, and B5 showed strong activity to Plasmodium falciparum, K1 strain (IC50 0.52–0.92 μM) and displayed anti- Bacillus cereus (MIC 1.56 μg/mL). Xanthoquinodin A6 also showed anti- Curvularia lunata (MIC 3.13 μg/mL). In addition, xanthoquinodins A4, A6, B4, and B5 and ketoxanthoquinodin A6 showed cytotoxicity against both cancerous (MCF-7, KB, NCI-H187) and non-cancerous (Vero) cells. Graphical abstract: Highlights: Eleven unknown xanthoquinodins were isolated from Cytospora eugeniae BCC42696. Chemical structures were determined by spectroscopic and mass spectrometric analyses. Absolute configurations of xanthoquinodins were assigned by CD analyses. Xanthoquinodins had broad spectrum of antimalarial and antibacterial activities.